(untitled) (Fiep Bulletin - online, 2015)
It was not until this century that the athletic world became interested in the phenomenon of systematic training which can improve one’s sports performance. The physiological sport literature seldom gives a concrete answer to the simple question of what training to the simple question of what training actually is. Asmussen & Christensen (1964) stand: “by training in meant a systematic practicing of one or another ability”.